2022
DOI: 10.3390/cancers14143539
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Substance P/Neurokinin-1 Receptor System in Cancer

Abstract: New, promising molecular targets to block tumor development and new compounds capable of specifically destroying cancer cells must be urgently investigated [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…It has been reported that the combination of chemotherapy and aprepitant protects various organs and counteracts the severe side-effects of chemotherapy (cardioprotection, nephroprotection, hepatoprotection, and neuroprotection) [ 39 , 40 , 41 , 42 ] and cytoprotection ([ 4 , 43 ] ( Figure 1 ). This combination therapy was also shown to induce tumor chemosensitization [ 4 , 5 , 43 ] ( Figure 1 ).…”
Section: Combination Of Chemotherapy and Aprepitant In Osteosarcoma T...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the combination of chemotherapy and aprepitant protects various organs and counteracts the severe side-effects of chemotherapy (cardioprotection, nephroprotection, hepatoprotection, and neuroprotection) [ 39 , 40 , 41 , 42 ] and cytoprotection ([ 4 , 43 ] ( Figure 1 ). This combination therapy was also shown to induce tumor chemosensitization [ 4 , 5 , 43 ] ( Figure 1 ).…”
Section: Combination Of Chemotherapy and Aprepitant In Osteosarcoma T...mentioning
confidence: 99%
“…It has been reported that the combination of chemotherapy and aprepitant protects various organs and counteracts the severe side-effects of chemotherapy (cardioprotection, nephroprotection, hepatoprotection, and neuroprotection) [ 39 , 40 , 41 , 42 ] and cytoprotection ([ 4 , 43 ] ( Figure 1 ). This combination therapy was also shown to induce tumor chemosensitization [ 4 , 5 , 43 ] ( Figure 1 ). Additionally, it was reported in an in vitro study using MG63.2 osteosarcoma cells that the combination therapy of an NK-1R antagonist, L-733,060 compound, and different chemotherapy drugs used in the treatment of osteosarcoma (doxorubicin, cisplatin, ifosfamide, and mitomycin) increased the anticancer activity of chemotherapy (chemosensititzation) [ 5 ] ( Figure 1 ).…”
Section: Combination Of Chemotherapy and Aprepitant In Osteosarcoma T...mentioning
confidence: 99%
“…One of these promising targets could be peptidergic systems, i.e., peptides and their receptors, which play a crucial role in cell communication. Peptidergic systems have opened up new research lines and possibilities to improve cancer diagnosis and explore new antitumor strategies [ 1 , 2 , 3 , 4 ]. The involvement of peptidergic systems in cancer has attracted increasing interest in the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of peptidergic systems in cancer has attracted increasing interest in the last few years. Peptides such as substance P (a full review focused on its participation in cancer was recently published [ 5 ]), neurotensin, orexin, angiotensin II, neuropeptide Y, vasoactive intestinal peptide, calcitonin gene-related peptide, adrenomedullin, adrenomedullin 2 or intermedin, and amylin contribute to cancer development [ 1 , 2 , 6 ]. These peptides promote the mitogenesis/migration of tumor cells, exert an antiapoptotic action, and stimulate the growth of blood vessels and lymphangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation